New formulation of a recombinant anthrax vaccine stabilised with structurally modified plant viruses - Granovskiy, Dmitriy L.; Ryabchevskaya, Ekaterina M.; Evtushenko, Ekaterina A.; Kondakova, Olga A.; Arkhipenko, Marina V.; Kravchenko, Tatiana B.; Bakhteeva, Irina V.; Timofeev, Vitalii S.; Nikitin, Nikolai A.; Karpova, Olga V. (Frontiers in Microbiology, 2022)
Anthrax is a disease caused by Bacillus anthracis. The most promising approach to the development of anthrax vaccine is use of the anthrax protective antigen (PA). At the same time, recombinant PA is a very unstable protein. Previously, the authors have designed a stable modified recombinant anthrax protective antigen with inactivated proteolytic sites and substituted deamidation sites (rPA83m). As a second approach to recombinant PA stabilisation, plant virus spherical particles (SPs) were used as a stabiliser. The combination of these two approaches was shown to be the most effective. Here, the authors report the results of a detailed study of the stability, immunogenicity and protectiveness of rPA83m+SPs compositions. These compositions were shown to be stable, provided high anti-rPA83m antibody titers in guinea pigs and were able to protect them from a fully virulent 81/1 Bacillus anthracis strain. Given these facts, the formulation of rPA83m+SPs compositions is considered to be a prospective anthrax vaccine candidate.